An Evaluation of the film one flew over the cuckoo's nest as a medium for the training of psychotherapists - Miller, Liizl Helen (University of Limpopo (Medunsa Campus), 2010)
The aim of the study is to analyse the film One flew over the cuckoo’s nest, from a clinical psychology perspective in order to evaluate the possible use of the film and significant concepts depicted therein in a training context. The objectives of the study are to describe the interactional dynamics of the psychiatric system as depicted in the film, to identify and describe the impact of the systems and/or subsystems on the psychotherapeutic growth of “patients” and to provide suggestions for the training of psychotherapists on the basis of the film and the present research. A qualitative, descriptive research design was used to achieve these aims. This allowed for systematic clinical descriptions by four clinical psychologists to be obtained. The study involved an exploration of relevant literature as well as an indepth study of a specific therapeutic group in interaction as depicted in the film. The film was shown to four clinical psychologists. Their findings were analysed, and common themes in their analyses identified. The researcher came to certain conclusions on the basis of the above-mentioned analyses. The findings of this study seem to indicate that the interactional style of the psychiatric staff, as portrayed in the film, contributed to the deterioration of the psychological well-being of the “patients”, thus inhibiting their psychological growth and promoting psychopathology. In spite of the findings, the researcher wishes to recommend the utilisation of this film as a training medium, on condition that a paradigm shift is made away from the traditional medical/psychiatric approach to a ii systems-based epistemology. This could result in viewing the psychiatric system as a hierarchy of interrelated subsystems-in-interaction, and open up possibilities for a redefinition of the various roles of those involved within the larger system. Further research in this direction is strongly indicated and recommended.
Thesis (MSc.(Clinical Psychology))University of Limpopo, 2010.
Keywords: cuckoo's nest; Psychotherapists; Psychotherapy; Psychotherapy, group